On the identity of Navicula gottlandica (Bacillariophyta), with the description of two new species Navicula eileencoxiana and Navicula bergstromiana from the Australo-Pacific region - Sabbe, Koen; Vyverman, Wim; Ector, Luc; Wetzel, Carlos; John, Jacob; Hodgson, Dominic; Verleyen, Elie; Van de Vijver, Bart (Meise Botanic Garden and Royal Botanical Society of Belgium, 2019)
Background and aims – During the past two decades, the subantarctic diatom flora has been the subject of several detailed taxonomic revisions, resulting in the description of a large number of new species. During a survey of the freshwater diatom flora of Macquarie Island (southern Pacific Ocean), an unknown Navicula species was observed showing resemblance to Navicula gottlandica . Populations of similar diatoms (previously reported as N. gottlandica ) from Tasmania were also investigated. We here present a detailed morphological analysis of these diatoms, and compare it with the type material of N. gottlandica . Methods –Materials were analysed using Light and Scanning Electron Microscopy. Key results –The southern hemisphere populations represent two hitherto unknown taxa here described as Navicula bergstromiana and N. eileencoxiana . Important morphological differences include valve shape, stria density, shape of the central area, ultrastructure of the external central raphe endings, presence of a distinct internal accessory rib, and the relative width of the external longitudinal silica strips covering the valve face with respect to the longitudinal fissures separating these strips. While the new taxa show some affinity with the genus Haslea , the internal apical structure of the raphe, the external structure of the terminal raphe fissures and the central raphe endings (often with tooth-like protrusions, creating the impression of a satellite pore), and the apparent lack of the typical sandwich-type Haslea valve ultrastructure support the position of N. gottlandica and both new taxa within the genus Navicula . Conclusions – The description of two additional species with close similarities to N. gottlandica (i.e. possessing the typical longitudinal striae/silica strips and tooth-like protrusions in hooked central raphe endings) suggests that the N. gottlandica species group is more diverse than previously thought. The existence of closely similar Navicula species recently described from rivers in tropical ...